A estabilização da tutela e seus reflexos ao litisconsorte passivo necessário - Esotico, Paola de Castro (2022)
The new Civil Procedure of Law published in 2015 included in its forecasts the institute of stabilization of the decision granting early protection and determined that this decision becomes stable when the defendant does not appeal of it. The new Civil Procedure of Law demonstrates legislator’s concern with the abbreviation of the procedure that needs urgent decisions stablishing that the author can plead it prior to the main lawsuit. Besides that, the legislator was also concerned about the effects propagated over the time by the aforementioned urgent decision, foreseeing the possibility of preserving its effects even if the lawsuit ends without analysis of the material law relationship. Considering the said stabilization of the decision depends on author’s lack of interest in continuing the dispute and, on the other hand, on a non-resistance of the defendant, we suggest in this study the investigation of the possibility of stabilization of the urgent decision and its respective effects when we are facing a lawsuit in which there is a plurality of subjects, since the general rule is the presence in the lawsuit of everyone who may be affected by the effects of the judicial sentence. Depending on the legal matter, the legislator may establish the mandatory integration of the process by more than one subject as an active or passive part of the lawsuit, as well as determine that the judicial provision must be unitary to all those involved in the same pole of the legal procedure, also foreseeing the consequences for the lawsuit in case of judge rules in favor or one part without the presence of all the necessary parties of the lawsuit. Considering that it would be impossible to exhaust such a thought-provoking theme in this study, we chose to center our analysis on the figure of the necessary passive co-consort and the consequences of the stabilization of the urgent decision for him, since, as briefly anticipated, stabilization can only operate when there is inertia of the defendant of the process